2010
DOI: 10.1108/13620431011020899
|View full text |Cite
|
Sign up to set email alerts
|

Proactivity, job characteristics, and engagement: a longitudinal study

Abstract: General rights Copyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.-Users may download and print one copy of any publication from the public portal for the purpose of private study or research-You may not further distribute the material or use it for any profit-making activity or commercia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
46
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 57 publications
6
46
1
1
Order By: Relevance
“…As regards the moderating effect of proactive personality, and contrary to Hobfoll (2001), we did not find that teachers with a proactive personality make better use of developmental opportunities. Since proactive personality has a strong and direct association with engagement and employability (see also Dikkers et al, 2010), it seems that proactive teachers are able to increase their engagement and employability irrespective of the development opportunities they are given. Future research should try to explain why or how proactive teachers increase their engagement and employabilityfor example through job crafting behaviors (Wrzesniewski and Dutton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…As regards the moderating effect of proactive personality, and contrary to Hobfoll (2001), we did not find that teachers with a proactive personality make better use of developmental opportunities. Since proactive personality has a strong and direct association with engagement and employability (see also Dikkers et al, 2010), it seems that proactive teachers are able to increase their engagement and employability irrespective of the development opportunities they are given. Future research should try to explain why or how proactive teachers increase their engagement and employabilityfor example through job crafting behaviors (Wrzesniewski and Dutton, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…There is considerable evidence regarding the positive effect of self-efficacy and proactive behaviour on psychological well-being and performance (Bandura, 1999(Bandura, , 2001Bateman & Crant, 1999;Crant, 1995;Dikkers, Jansen, de Lange, Vinkenburg, & Kooij, 2010;Frese & Fay, 2001;Harter, 2000). Proactive people scan for opportunities, show initiative, take action, and persevere until they have achieved what they intend, bringing about change (Bateman & Crant, 1993).…”
Section: Mastenbroek Et Almentioning
confidence: 99%
“…Dickers, Jansen, de Lange, Vinkenburg and Kooij (2010) found that an entrepreneurial personality is associated with increased engagement and thereby better performance. McKenna (1996) concluded that entrepreneurs can sometimes negatively affect performance of a firm through the "dark side" of their personality.…”
Section: Linking Personality and Performancementioning
confidence: 99%